(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The Right to Education (RTE) Act, 2009, is a watershed moment in India’s educational history since it guarantees all children, from the ages of 6 to 14, the right to free and compulsory education. This study takes a close look at RTE and how it has influenced social change by promoting equity, human development, and better access. Key outcomes such as improved enrolment, better engagement of marginalised groups, and progress toward decreasing gender & socio-economic inequality are evaluated in the study utilising a doctrinal and analytical research strategy based on secondary data. At the same time, the paper highlights major challenges that limit the transformative potential of RTE, including declining learning outcomes, inadequate infrastructure, persistent inequalities, and weak governance mechanisms. The findings reveal that while the Act has been successful in expanding access to education, it has not adequately addressed issues related to quality and effective implementation. The study concludes that for RTE to function as a true catalyst of social transformation, policy reforms must prioritize learning outcomes, strengthen institutional capacity, and ensure inclusive and equitable delivery of education. A balanced focus on both access and quality is essential for achieving sustainable socio-economic development.